Prevalence and incidence of early childhood caries among African‐American children in Alabama. (11th September 2014) - Ghazal, Tariq; Levy, Steven M.; Childers, Noel K.; Broffitt, Barbara; Cutter, Gary; Wiener, Howard W.; Kempf, Mirjam; Warren, John; Cavanaugh, Joseph
Abstract Objectives This study aims to assess the prevalence and incidence of early childhood caries (ECC) in African‐American children. Methods A cohort of 96 African‐American children approximately 1 year of age at baseline were recruited in Uniontown, Alabama, and followed for 3 years. Oral examinations were conducted annually by one of three trained/calibrated dentists using portable equipment, without radiographs, following WHO criteria. Results The prevalence of decayed/missing/filled surfaces (dmfs) was: 1.1 percent (all d) at approximately age 1 (n = 90, six children were excluded for having no erupted teeth); 12.8 percent (d = 10.5 percent & f = 4.7 percent) at age 2 (n = 86); 39.3 percent (d = 21.4 percent, m = 2.4 percent & f = 22.6 percent) at age 3 (n = 84); and 65.8 percent (d = 28.8 percent, m = 5.5 & f = 46.6 percent) at age 4 (n = 73). The percentages of incisors, canines, first molars, and second molars with dmfs were: 0.1 percent, 0.0 percent, 0.0 percent, and 0.0 percent, at age 1; 2.4 percent, 0.1 percent, 0.8 percent, and 0.6 percent at age 2; 8.2 percent, 0.8 percent, 7.6 percent, and 6.3 percent at age 3; and 10.2 percent, 2.2 percent, 12.6 percent and 16.7 percent at age 4, respectively. The three, 1‐year, person‐level incidence rates were 12.8 percent (age 1 to age 2), 38.6 percent (age 2 to age 3), and 56.2 percent (age 3 to age 4). From baseline, the 2‐year incidence was 39.3 percent and 3‐year incidence was 65.8 percent, whereas the 2‐year caries incidence from age 1 to age 3 was 66.7 percent (n = 72). Conclusion The majority of children developed caries during the 3‐year follow‐up, which is much higher than the 32 percent prevalence of caries among African‐American children under age 6 years in National Health and Nutrition Examination Survey from 1999 to 2002.